2001
DOI: 10.1161/01.cir.103.9.1264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Birth Weight and Cardiovascular Risk Factors on Endothelial Function in Early Adult Life

Abstract: Background-Low birth weight is related to increased risk of coronary heart disease in adults and recently has been associated with vascular endothelial dysfunction in children. We investigated whether the relation between birth weight and endothelial function was still present in early adult life and whether there was an interaction with emerging risk factors. Methods and Results-In 315 adults (165 women, 150 men, aged 20 to 28 years), high-resolution ultrasound was used to determine endothelium-dependent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
2
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(230 citation statements)
references
References 37 publications
7
210
2
11
Order By: Relevance
“…Adults known to have had intrauterine growth retardation have been shown to exhibit abnormalities of peripheral endothelial function. 327 Remarkably, adults with low birth weight who otherwise had a low-risk cardiovascular profile (nonsmoker, normal blood pressure, and normal weight) have been shown to have vascular dysfunction similar to the risk of individuals who smoked 4.5 cigarette pack-years. 328 Genetic-environment interactions are ubiquitous in human development.…”
Section: Effect Of Prenatal/early Childhood Deprivation On Cvd Incidementioning
confidence: 99%
“…Adults known to have had intrauterine growth retardation have been shown to exhibit abnormalities of peripheral endothelial function. 327 Remarkably, adults with low birth weight who otherwise had a low-risk cardiovascular profile (nonsmoker, normal blood pressure, and normal weight) have been shown to have vascular dysfunction similar to the risk of individuals who smoked 4.5 cigarette pack-years. 328 Genetic-environment interactions are ubiquitous in human development.…”
Section: Effect Of Prenatal/early Childhood Deprivation On Cvd Incidementioning
confidence: 99%
“…A recent study has shown a relationship between low birth weight and endothelial dysfunction in young adults that was most marked in individuals with lower risk factor profiles. This suggests that the association does not operate via increased risk factors, such as cholesterol and blood pressure, and that early growth may directly influence the blood vessel wall (Leeson et al, 2001). Further studies are needed to understand fully the different pathways in programming of adult diseases.…”
Section: Figurementioning
confidence: 99%
“…7,25,29 All of the adolescents in the present study were born fullterm and with adequate weight, however we do not have information on their rates of growth during their first weeks of life (Table 1). …”
Section: Variablesmentioning
confidence: 99%
“…5 Studies have found evidence of abnormal endothelial function in people with risk factors for arterial hypertension and atherosclerosis, such as obesity, familial hypercholesterolemia, family history of arterial hypertension and low birth weight. [6][7][8] These studies assessed endothelial function by means of high-resolution B-mode ultrasound, a methodology that is widely used to evaluate endotheliumdependent vascular dilatation. This dilatation is a function of NO, which is a potent vasodilator and is produced by endothelial cells in response to stimulation from blood in contact with the vessel walls.…”
Section: Introductionmentioning
confidence: 99%